Ticagrelor as an alternative in clopidogrel-associated neutropenia. (February 2015) - Shah, Rahman; Keough, Leigh Anne; Belalcazar-Portacio, Astrid; Ramanathan, Kodangudi B.
Abstract Aspirin in combination with platelet P2Y12 receptor blocker has become the mainstay antiplatelet treatment strategy for the prevention of stent thrombosis. Ticlopidine was the first widely used P2Y12 receptor blockers, but clopidogrel has mostly replaced the use of ticlopidine due to its more favorable adverse event profile on bone marrow. However, when clopidogrel induced bone marrow toxicity occurs, little is known about the efficacy and safety of alternative treatments, and thus, in these cases, medical decisions may be very difficult. We report a case of clopidogrel-induced severe neutropenia in a patient treated with coronary stent and safety of alternative treatment with ticagrelor.